2015
DOI: 10.1002/jssc.201500462
|View full text |Cite
|
Sign up to set email alerts
|

Determination of lansoprazole enantiomers in dog plasma by column‐switching liquid chromatography with tandem mass spectrometry and its application to a preclinical pharmacokinetic study

Abstract: Lansoprazole, a selective proton pump inhibitor, has a chiral benzimidazole sulfoxide structure and is used for the treatment of gastric acid hypersecretory related diseases. To investigate its stereoselective pharmacokinetics, a column-switching liquid chromatography with tandem mass spectrometry method was developed for the determination of lansoprazole enantiomers in dog plasma using (+)-pantoprazole as an internal standard. After a simple protein precipitation procedure with acetonitrile, matrix components… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Finally, the mobile phase with a combination of 10 mM ammonium acetate and ACN gives better separation and good peak shape for lansoprazole and its degradation products (DP 1-8). The linear gradient program is as follows: (Tmin/% proportion of solvent B): 0-5 /10, 5-7 /30, 7-14 /40, [14][15][16][17][18][19][20] /45, 20-30 /45, [30][31][32][33][34][35] /50, 35-37 /70, 37-38 /10, 38-40 /10. The column temperature, flow rate, injection volume and detector wavelength were at 30°C, 1.0 ml/min, 20.0 μl and 285 nm, respectively.…”
Section: Methods Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the mobile phase with a combination of 10 mM ammonium acetate and ACN gives better separation and good peak shape for lansoprazole and its degradation products (DP 1-8). The linear gradient program is as follows: (Tmin/% proportion of solvent B): 0-5 /10, 5-7 /30, 7-14 /40, [14][15][16][17][18][19][20] /45, 20-30 /45, [30][31][32][33][34][35] /50, 35-37 /70, 37-38 /10, 38-40 /10. The column temperature, flow rate, injection volume and detector wavelength were at 30°C, 1.0 ml/min, 20.0 μl and 285 nm, respectively.…”
Section: Methods Developmentmentioning
confidence: 99%
“…It is used to treat and prevent ulcer, Zollinger-Ellison syndrome and erosive esophagitis. Few HPLC methods have been reported for the determination of lansoprazole in plasma [15,16] and quantification of (R)-(+)-and (S)-(À)-lansoprazole enantiomers and related impurities. [17] Few studies have been reported on the characterization of acidic [18] and hydrolytic degradation products.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence of the numerous merits of R-(+)-lansoprazole, such as the slower metabolism, higher plasma concentration, longer elimination half-time and greater systemic exposure, it was developed and approved for marketing as a novel proton-pump inhibitor with the trade name Dexilant in 2009 (Gomes, Cassiano, Pedrazzoli, & Cass, 2010;Hershcovici, Jha, & Fass, 2011;Katsuki, Hamada, Nakamura, Arimori, & Nakano, 2001;Metz, Vakily, & Dixit, 2009). Wang et al reported a column-switching LC-MS/MS method for the quantification of lansoprazole enantiomers in dog plasma, while the column-switching procedure required complicated and specific equipment (Wang et al, 2015). Additionally, the sample extraction of those methods was not ideal for high-throughput bioanalysis.…”
Section: Introductionmentioning
confidence: 99%
“…LC-MS/MS has became increasingly prevalent in biochemical analysis owing to its better sensitivity and selectivity, and its ability to provide high sample throughput (De et al, 2010;Wang et al, 2014). Wang et al reported a column-switching LC-MS/MS method for the quantification of lansoprazole enantiomers in dog plasma, while the column-switching procedure required complicated and specific equipment (Wang et al, 2015). In addition, it is still unclear whether or not the chiral switch between R-(+)-and S-(−)-lansoprazole in rat plasma samples exists, and the pharmacokinetics of dexlansoprazole and racemic lansoprazole after oral administration in rat have not been compared.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al. reported a column‐switching LC–MS/MS method for the determination of lansoprazole enantiomers in dog plasma. However, the column‐switching procedure required specific equipment and this method was not validated for human pharmacokinetic study.…”
Section: Introductionmentioning
confidence: 99%